Experimental Studies on Locally Produced Insecticide (Ota-piapia) - , O. G. Dawodu; , K. A. Oyekunle; , A. N. Masopa (Archives of Current Research International, 2019)
Introduction: Nigeria, like most countries worldwide find insect pest control a problem, unfortunately, the insecticides available are somewhat costly to the general populace, hence the dependence on the cheaply produced and widely available local insecticide famously called ‘Ota piapia’ literally translating to kill and dry. This study was carried out to determine the safety of ‘Ota piapia’ using Wistar rats as an animal model. Materials and Methods: Fifteen rats were divided into five groups and exposed dermally to 0%, 25%, 50%, 75% and 100% of insecticide concentrations respectively. Evaluation of their behaviour, haematological indices, liver enzyme {alkaline phosphatase (ALP), alanine aminotransferase (ALT), aspartate aminotransferase (AST)} and gas chromatography mass spectrometry (GC-MS) analysis of the insecticide was used as experimentally indices in evaluating safety limits of the local insecticide. Results: Behaviorally, the rats with higher concentrations of insecticide application showed acute signs of toxicity, with an increase in pack cell volume (PCV%) and lymphocyte and decrease in (total white blood cell count (TWBC) and neutrophils counts hematologically. There was a dose-dependent relationship between insecticide concentration and ALT and ALP activities, while this was not consistent with AST activity. The GC-MS analysis of the insecticide gave 43 components; mainly organic compounds with dichlorvos its main active component, having the highest percentage of 12.74%. Conclusion: Increased PCV%, decreased TWBC and neutrophil counts established in this study and its significant adverse effect on the serum level of liver enzymes implied that the local insecticide ota-pia pia is toxic and must be used with caution.